Registration of 'CP 13‐4474' sugarcane for sand soils. Issue 1 (7th November 2022) - Islam, Md S.; Sandhu, Hardev S.; Zhao, Duli; Sood, Sushma; Momotaz, Aliya; Baltazar, Miguel; Arbelo, Orlando Coto; Davidson, R. Wayne; Gordon, Vanessa S.
Abstract: 'CP 13‐4474' (Reg. no. CV‐209, PI 700305) sugarcane cultivar (a complex hybrid of Saccharum spp.) was released to growers in June 2021 for cultivating on sand soils in Florida after a decade‐long advancement through cooperative research conducted by the USDA‐ARS, the Florida Sugar Cane League Inc., and the University of Florida. It originated from a poly‐cross at Canal Point (CP). The Florida Sugarcane Variety Committee released CP 13‐4474 due to its high sugar yields, sucrose content on sand soils, and acceptable disease resistance. CP 13‐4774 has demonstrated resistance to brown rust (caused by Puccinia melanocephala H. & P. Sydow), orange rust (caused by Puccinia kuehnii E.J. Butler), mosaic (caused by Sugarcane mosaic virus strain E), and ratoon stunt (caused by Leifsonia xyli subsp. xyli Evtushenko et al.) and moderate resistance to smut [caused by Sporisorium scitamineum (Syd.) M. Piepenbr. et al.], leaf scald (caused by Xanthomonas albilineans Ashby, Dowson), and yellow leaf syndrome (caused by Sugarcane yellow leaf virus ). In late‐stage yield trials, CP 13‐4474 sugar yields were 9.4% greater than that of the check variety 'CL 88‐4730', while sucrose yields did not differ significantly from the reference check 'CP 96‐1252'. CP 13‐4474 displayed superior resistance to both brown and orange rusts and produced more commercial recoverable sucrose than all three tested reference checks over the same harvest trials. With its demonstrated resistance to diseases and elevated sugar production capacity, CP 13‐4474 is expected to positively influence both sugarcane production and crop sustainability in Florida. Core Ideas: A sugarcane cultivar was released to growers for cultivating on sand soils in Florida. The new cultivar has higher broad‐spectrum disease resistance. CP 13‐4474 showed elevated sugar production capacity. It is expected to positively influence both sugarcane production and crop sustainability in Florida.